Simulation of MC-DS-CDMA-System Based on: Wavelet and Slantlet Transforms over Wireless Channel - Abdel Hadi Fadhel, Ahmed (University of Thi-Qar Journal of Science, 2019)
In this paper two proposed schemes for improving the performance form the Bit Error Rate (BER) view point were proposed for Multicarrier-Direct-Sequence- Code Division Multiple Access (MC-DS-CDMA) system in wireless channel. The conventional MC-DS-CDMA-system is based on Fast Fourier Transform (FFT). One of the proposed systems was based on Wavelet transform (WT). The other system was based on Slantlet transform (SLT). Simulation is done in three different types of channels. Simulation results show that the two proposed systems outperform the conventional system. Also the MC-DS-CDMA-system which is based on SLT achieves the same performance with less filter lengths than the MC-DS-CDMA-system based on WT.